Kinerja Perawat di Ruang Rawat Inap RSUD Bima - Gazali, Zulkarnain (Business Management, 2022)
Quality health services can only be realized with the benefits of professional health services, as well as nursing care should be done with professional nursing practice. The function of motivation, communication, supervision, delegation and conflict management function can improve nurse's performance in applying nursing care. This research can be done by overcoming the nursing care in hospital wards RSUD Bima. This research use descriptive research design with cross sectional approach. The instrument used is questionnaire. The number of research samples was 86 nurses who were in 7 inpatient wards taken at random. The data analysis process used a chi-square test to determine the relationship with performance, and some lig- istical regression tests applied the most severe variables associated with nurse performance. The results showed that the variable of directive function (motivation pv = 0,005, communication pv = 0,019 supervision pv = 0,006 delegate pv = 0,026, conflict management pv = 0,004) relate to nurse performance with confounding variable (age, sex, marital status, occupation and Education) has no relationship with the performance of nurses. The majority of nurses apply a well-headed room head function. The most severe variable to the performance of the nursing service is the conflict management function